2021
DOI: 10.1016/j.fsi.2021.10.025
|View full text |Cite
|
Sign up to set email alerts
|

microRNAs facilitate comprehensive responses of Bathymodiolinae mussel against symbiotic and nonsymbiotic bacteria stimulation

Abstract: Background:As the dominant species inhabiting both cold seeps and hydrothermal vents,Bathymodiolinae mussels are one of the most successful megafauna in the deep sea.They thrive in dark and food-insu cient environmentsby harboring sulfur-oxidizing bacteria (SOB)and/or methaneoxidizing bacteria (MOB)ingill bacteriocytesand obtain the majority of their nutrition from them.Many attempts have been made to decode the mechanisms underlying their symbiosis, which yetremained largely undisclosedfor years due to the la… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…Pattern recognition receptors (PRRs) are important for immune recognition and response ( Byeon et al, 2015 ; Graça, 2015 ). Previous studies have reported high levels of PRRs in the symbiotic gill tissue of bathymodiolines, such as G. platifrons , B. septemdierum , and B. azoricus ( Bettencourt et al, 2014 ; Chen et al, 2021 ; Ikuta et al, 2019 ; Li et al, 2020 ; Wang et al, 2019 ), suggesting their importance in symbiosis. Both TLRs and PGRPs have been suggested to participate in endosymbiont establishment and symbiosis regulation ( Li et al, 2021 ; Sun et al, 2017 ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Pattern recognition receptors (PRRs) are important for immune recognition and response ( Byeon et al, 2015 ; Graça, 2015 ). Previous studies have reported high levels of PRRs in the symbiotic gill tissue of bathymodiolines, such as G. platifrons , B. septemdierum , and B. azoricus ( Bettencourt et al, 2014 ; Chen et al, 2021 ; Ikuta et al, 2019 ; Li et al, 2020 ; Wang et al, 2019 ), suggesting their importance in symbiosis. Both TLRs and PGRPs have been suggested to participate in endosymbiont establishment and symbiosis regulation ( Li et al, 2021 ; Sun et al, 2017 ).…”
Section: Discussionmentioning
confidence: 97%
“…C1qs may bind to the surface of pathogens and kill them directly or trigger downstream immune activities ( Jiang et al, 2015 ; Cheng et al, 2019 ). Consequently, C1qs have been suggested to function as scaffolds of PRRs and in symbiont recognition ( Chen et al, 2021 ). Wang et al ( 2021 ) reported high expression of C1qs in the gill tissue of G. platifrons .…”
Section: Discussionmentioning
confidence: 99%